Doubling maize (Zea mays) production of India by 2025 – Challenges and opportunities - YADAV, O P; PRASANNA, B M; YADAVA, P; JAT, S L; KUMAR, D; DHILLON, B S; SOLANKI, I S; SANDHU, J S (The Indian Journal of Agricultural Sciences, 2016)
Maize (Zea mays L.) is a commodity of high economic significance in India. Its demand and production is increasing more rapidly as compared to other major commodities. It is estimated that by 2025, India would require 50 million metric tonnes (MMT) maize grain, of which 32 MMT would be required in the feed sector, 15 MMT in the industrial sector, 2 MMT as food, and 1 MMT for seed and miscellaneous purposes. Over this, there would be about 10 MMT of export potential also. Thus, in the next 10 years there is a necessity and opportunity for doubling India’s maize production from the current level of approximately 25 MMT. Prevalence of yield limiting biotic and abiotic stresses, lower adoption of modern production technologies in certain regions, extension and policy gaps, etc. remain major challenges before the Indian maize sector. Therefore, strong technological and policy interventions would be required to achieve the goal of doubling maize production. By 2025, productivity level of 5-6 tonnes/ha need to be targeted, in order to double the production without significant increase in acreage. Technological interventions like cultivar development and diversification, incorporation of stress resilience in the germplasm, accelerating the breeding process through new tools, and adoption of modern cultivation and protection practices including conservation agriculture technologies would play a key role in increasing the productivity. At the same time, policy interventions like strengthening of post-harvest handling infrastructure, price stabilization mechanisms, and value chains, streamlining of extension system, augmenting hybrid seed delivery mechanisms, appropriate policy on genetically modified seeds etc. will be essentially required.